2021
DOI: 10.1016/j.annonc.2021.01.071
|View full text |Cite
|
Sign up to set email alerts
|

Second-line nivolumab in relapsed small-cell lung cancer: CheckMate 331☆

Abstract: Background: Patients with relapsed small-cell lung cancer (SCLC) have few treatment options and dismal survival. Phase I/II data show activity of nivolumab in previously treated SCLC.Patients and methods: CheckMate 331 is a randomized, open-label, phase III trial of nivolumab versus standard chemotherapy in relapsed SCLC. Patients with relapse after first-line, platinum-based chemotherapy were randomized 1 : 1 to nivolumab 240 mg every 2 weeks or chemotherapy (topotecan or amrubicin) until progression or unacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
156
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(172 citation statements)
references
References 28 publications
(35 reference statements)
4
156
0
1
Order By: Relevance
“…Prospective trials revealed that CPS score did not predict PFS with Pembro or nivolumab. 9,13 In this study, patients with CPS greater than or equal to 1% or TIL 3þ tended to have slightly better outcomes, but not statistically significant. Gay et al 15 recently proposed four subtypes of SCLC on the basis of transcription factors and the inflamed subtype revealed higher sensitivity to ICI plus chemotherapy.…”
Section: Discussionmentioning
confidence: 48%
“…Prospective trials revealed that CPS score did not predict PFS with Pembro or nivolumab. 9,13 In this study, patients with CPS greater than or equal to 1% or TIL 3þ tended to have slightly better outcomes, but not statistically significant. Gay et al 15 recently proposed four subtypes of SCLC on the basis of transcription factors and the inflamed subtype revealed higher sensitivity to ICI plus chemotherapy.…”
Section: Discussionmentioning
confidence: 48%
“…There were five treatment-related death, two with nivolumab and three with chemotherapy. The incidences of irAEs (all grade) of endocrine, skin, gastrointestinal, liver, lung and kidney were 12, 11, 7, 5, 1 and <1% respectively (32). In study CheckMate-032, skin toxicity (any grade, 21.1%) was the most common.…”
Section: Nivolumabmentioning
confidence: 93%
“…In IFCT-1603 study, atezolizumab monotherapy was compared with topotecan or re-induction of initial chemotherapy (31). A phase III trial CHECKMATE-331 investigated the efficacy and safety of nivolumab monotherapy in the second line of therapy (32). Both trials demonstrated no superiority of immunotherapy over traditional chemotherapy.…”
Section: Second Linementioning
confidence: 99%
“…73,74 In addition, the phase III RCT, CheckMate 331, comparing nivolumab to topotecan (or amrubicin) as second-line treatment in unselected (platinum-sensitive and -resistant) patients with stage IV SCLC and a PS of 0-1 failed to demonstrate an improvement in OS, PFS or ORR for nivolumab versus ChT. 75 Limited efficacy was also seen in the phase II French Cooperative Thoracic Intergroup 16-03 trial evaluating atezolizumab in relapsed SCLC (N Q14 ¼ 73); the disappointing ORR (2.3%) and median PFS (1.4 months) following immunotherapy precluded activation of the phase III part of the study. 76 The combination of cytotoxic T-lymphocyte-associated protein 4 and PD-L1 blockade is being evaluated in several ongoing trials.…”
Section: Standard Treatmentmentioning
confidence: 99%